2022
DOI: 10.1111/iju.14915
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and varicocele among 211 989 Chinese reproductive‐age males

Abstract: Objectives: To explore the relationship between body mass index and varicocele, the range of body mass index that leads to increased odds of varicocele, and the association between body mass index with the position and grade of varicocele. Methods: We conducted a cross-sectional study of 211 989 Chinese males aged 18-65 years participated in the National Free Pre-conception Check-up Projects from January 2013 to December 2018. Univariate and multivariate logistic regression models were constructed to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similarly, whether or not obesity can increase the risk of varicocele has not been completely clarified. Accordingly, some studies have found a positive correlation between BMI and an increased varicocele risk, 94–96 other authors have reported no association or even a negative correlation 97–100 . Interestingly, however, Garolla et al 101 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, whether or not obesity can increase the risk of varicocele has not been completely clarified. Accordingly, some studies have found a positive correlation between BMI and an increased varicocele risk, 94–96 other authors have reported no association or even a negative correlation 97–100 . Interestingly, however, Garolla et al 101 .…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, some studies have found a positive correlation between BMI and an increased varicocele risk, [94][95][96] other authors have reported no association or even a negative correlation. [97][98][99][100] Interestingly, however, Garolla et al 101 showed that both obesity and varicocele are associated with a significant increase in 24-h mean scrotal temperature when compared to controls. In addition, other authors have reported that obesity negatively affects varicocelectomy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prevalence may have geographic differences in countries. Among 211,989 Chinese males of reproductive age and an average age of 31.20 years, a prevalence of 7.66% was observed [ 9 ]. There was an incidence of 15.7% in 7035 European young men with a median age of 19 years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%